2014
DOI: 10.5755/j01.em.18.4.4990
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Perception of Lithuanian Eco-Label

Abstract: In the recent decade, individuals have become more environmentally concerned, while companies realized that consumers' needs and desires are changing. This, in turn, has created new environmentally oriented practices, like ecological labeling, to satisfy consumer demands. Though eco-labels were created with a purpose to ease consumers to make their buying choices, a certain degree of confusion has emerged among the customers concerning the precise meaning of ecolabels. In Lithuania "Ekologinis žemės ūkis" ("Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In their study on Lithuanian consumers, Kavaliauske et al (2013) found that buying choices were not driven or influenced by the presence of ecolabels (apart from a few consumer niches; Karlsson & Dolnicar, 2016), likely because they knew little about them. Aarset et al (2004) found that consumers' trust in ecological schemes was low, although their investigation of customers' reactions to green behaviors revealed a positive reaction toward companies that were adopting virtuous behaviors (Han et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study on Lithuanian consumers, Kavaliauske et al (2013) found that buying choices were not driven or influenced by the presence of ecolabels (apart from a few consumer niches; Karlsson & Dolnicar, 2016), likely because they knew little about them. Aarset et al (2004) found that consumers' trust in ecological schemes was low, although their investigation of customers' reactions to green behaviors revealed a positive reaction toward companies that were adopting virtuous behaviors (Han et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In general, ecolabels provide information on products and services and can be used as a powerful marketing tool (Kavaliauske, Vaskiv, & Seimiene, 2013), as they communicate how companies operate at a quality and environmental level (Grunert, 1993). However, the research suggests that it is difficult to evaluate customers' overall reaction to ecolabels in the tourism sector, as well as in other sectors considerable efforts that have been made at the EU level to promote and support certification (D'Alessandro & Masoni, 2015).…”
Section: Point Of View Of Hospitality Sector Managers and Consumer Perceptions Of Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, evidence is mounting that in ex-communist societiesa category that, of course, includes Polandthings are aggravated by the legacy of the past. Research by Bruschi et al (2015) and Kavaliauske et al (2013) bears this assumption out. Bruschi et al (2015) investigated the knowledge of food certification in Russia, where "mistrust might be explained by the fact that corruption in Russia, as well as in other former communist countries, was widespread during the early years of transition and strongly affected the market" (p. 422).…”
Section: Consumer Recognition Of Certification Trademarks and Its Implicationsmentioning
confidence: 99%
“…According to the COI (2007), these include for instance supporting local farmers and local business, cutting down on pollution and reducing the purchase power of supermarket chains. On the other hand, according to Lithuanian research people do not believe that buying environmentallyfriendly products can make a difference to the environment (Kavaliauskė et al, 2013).…”
Section: Local Foodmentioning
confidence: 99%